What’s in a name? Where’s the person in personalized medicine? - Chadwick, Ruth Felicity (Lato Sensu: Revue de la Société de philosophie des sciences, 2018)
Medicine is said to be moving rapidly down the road towards personalization, but it is not entirely clear how we are to understand this term, or its implications for ethics. In understanding the concept of personalized medicine there are multiple possible interpretations of ‘personalization’ at stake. These may in turn presuppose different concepts of ‘person’, with resulting variations in the ethical implications.